2017
DOI: 10.1111/jpc.13657
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for neck and shoulder pain among schoolchildren and adolescents

Abstract: Aim: To evaluate the potential risk factors for neck and shoulder pain among schoolchildren. Methods: Demographic, physical/leisure activity, school-related and psychosocial factors for neck/shoulder pain were evaluated in a crosssectional study of 1611 schoolchildren aged 11-14 years. Results: Neck and shoulder complaints were reported in 27.9 and 19.0% of the sample, respectively. According to multivariate logistic regression models, high desk height (odds ratio (OR) = 2.23, 95% confidence interval (CI): 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 21 publications
5
39
0
Order By: Relevance
“…Musculoskeletal disorders are very common health problem in all age groups and genders throughout the world (Vos T et al, 2012). Recent evidence suggests that musculoskeletal disorders are very common in school children and adolescents (Dianat et al, 2017). This has become a major health problem and has burdened people and communities (Shan et al, 2013;Scarabottolo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal disorders are very common health problem in all age groups and genders throughout the world (Vos T et al, 2012). Recent evidence suggests that musculoskeletal disorders are very common in school children and adolescents (Dianat et al, 2017). This has become a major health problem and has burdened people and communities (Shan et al, 2013;Scarabottolo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of LBP has been reported to exceed more than 50% among those who watched TV for more than 2 hours a day [41]. Similar findings have indicated that the situation is aggravated when wat ching TV is accompanied by sitting in a relatively static position for a long time, unsuitable sitting postures, and low levels of PA [42,43].…”
Section: Discussionmentioning
confidence: 94%
“…The mean weight of the participants were 49.7 (SD 11.36) kg; [girls ≤13 years: 48.1 (SD 10.5) kg, girls ≥14 years: 47.2 (SD 11.7) kg, boys ≤13 years: 51.1 (SD 10.1) kg and boys ≥14 years: 53.2 (SD 12.2) kg] and BMI, 19.9 (3.83) kg/m 2 [girls ≤13 years: 19.6 (SD 3.8) kg/m 2 , girls ≥14 years: 20.0 (SD 4.2) kg/m 2 , boys ≤13 years: 19.8 (SD 3.3) kg/m 2 and boys ≥14 years: 20.3 (SD 4.0) kg/m 2 ]. More details on characteristics of the physical leisure activity, use of schoolbags and psychological trait among the schoolchildren are presented in [ 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, as in any epidemiological study, there may be possible limitation with regard to the accuracy and reliability of self-reported data on MSP as the outcome measure. However, as it has been acknowledged, this may be the only measure to understand whether and how the school children and adolescents feel any pain or discomfort, especially in large-scale populations [ 5 , 14 ]. As another limitation, we performed the LCA in a cross-sectional study and have focused on gender- and age-specific MSP clusters in the population but we didn’t taking into account the risk factors; to better find the relationship between the risk factors and MSP combinations in a LCA scheme, stronger epidemiological studies (case-control and cohort designs) are recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation